Genetic Analysis of Adult Plant Resistance to Stripe Rust in Common Wheat Cultivar “Pascal” - Bai, Bin; Li, Zimeng; Wang, Hongmei; Du, Xiaolin; Wu, Ling; Du, Jiuyuan; Lan, Caixia (Frontiers in Plant Science, 2022)
Wheat stripe rust is an important foliar disease that affects the wheat yield globally. Breeding for resistant wheat varieties is one of the most economically and environmentally effective ways to control this disease. The common wheat (Triticum aestivum L.) cultivar “Pascal” exhibited susceptibility to stripe rust at the seedling stage but it showed high resistance to stripe rust at the adult plant stage over 20 years in Gansu, a hotspot of the disease in northwestern China. To understand the genetic mechanism of stripe rust resistance in this cultivar, a 55K SNP array was used to analyze the two parents and the 220 recombinant inbred lines (RILs) derived from the cross of “Huixianhong” × “Pascal.” We detected three new stripe rust adult plant resistance (APR) quantitative trait locus (QTL) contributed by Pascal, viz. QYr.gaas-1AL, QYr.gaas-3DL, and QYr.gaas-5AS, using the inclusive composite interval mapping method. They were flanked by SNP markers AX-111218361—AX-110577861, AX-111460455—AX-108798599, and AX-111523523—AX-110028503, respectively, and explained the phenotypic variation ranging from 11.0 to 23.1%. Bulked segregant exome capture sequencing (BSE-Seq) was used for fine mapping of QYr.gaas-1AL and selection of candidate genes, TraesCS1A02G313700, TraesCS1A02G313800, and TraesCS1A02G314900 for QYr.gaas-1AL. KASP markers BSE-1A-12 and HXPA-3D for QYr.gaas-1AL and QYr.gaas-3DL were developed for breeders to develop durable stripe rust-resistant wheat varieties.